Sass Béla élete és munkássága - Koncz-Vágási, Katalin (Gerundium, 2015)
BÉLA SASS REKTOR. His father was a Reformist priest in Albis, Bihar County and the padre of General József Nagysándor in 1848–49. After inishing his theology studies, he worked as a religion teacher at the Debrecen Grammar school for a short period of time. From 1890, he was a teacher of Old Testament readings at the heology Academy of the Debrecen Reformist College. Between 1895–98 he was the Director of the Academy. At the recently established University of Debrecen he worked as the professor of Old Testament readings and related studies from 1914 until his death. Within this time period, he was the Dean of the Faculty of Reformist heology in 1915–16 and in 1926–27, and the Rector in 1921–22. He published numerous essays in relation to the Old Testament and to the history of the Reformist church and wrote philosophy books, as well.